Pest Status of the Brown Marmorated Stink Bug, Halyomorpha Halys in the USA. (1st October 2012) - Leskey, Tracy; Hamilton, George; Nielsen, Anne; Polk, Dean; Rodriguez-Saona, Cesar; Bergh, J. Christopher; Herbert, D. Ames; Kuhar, Tom; Pfeiffer, Douglas; Dively, Galen; Hooks, Cerruti; Raupp, Michael; et al.
Since its initial discovery in Allentown, PA, USA, the brown marmorated stink bug (BMSB), Halyomorpha halys (Heteroptera: Pentatomidae) has now officially has been detected in 38 states and the District of Columbia in the USA. Isolated populations also exist in Switzerland and Canada. This Asian species quickly became a major nuisance pest in the mid-Atlantic USA region due to its overwintering behavior of entering structures. BMSB has an extremely wide host range in both its native home and invaded countries where it feeds on numerous tree fruits, vegetables, field crops, ornamental plants, and native vegetation. In 2010, populations exploded causing severe crop losses to apples, peaches, sweet corn, peppers, tomatoes and row crops such as field corn and soybeans in several mid-Atlantic states. Damaging populations were detected in vineyards, small fruit and ornamentals. Researchers are collaborating to develop management solutions that will complement current integrated pest management programs. This article summarizes the current pest status and strategies being developed to manage BMSB in the USA.